Modelo de estructura organizacional de la Papelería Otavalito en la Parroquia Miguel Egas, Cantón Otavalo, Provincia Imbabura. - Córdova Quinchiguango, Jenny Marianela (2015)
An organizational structure is the base of operations of every business, the lack of it is the cause of all internal problems according to research advanced by Henry Fayol. In the stationery Otavalito has been done a diagnosis by the methods of deductive and analytical research and research tools such as surveys and interviews, which was determined the need for Stationery Otavalito to have an organizational structure model to be performed well. Therefore we have developed a management model consists of a vertical model of organizational structure based on the basic operations; a model which of human resource management based on modern people management; and organization of point of sale and improving the presentation of products through the methodology of Merchandising. The proposal aims to increase efficiency and effectiveness in the internal operations of stationery to solve the main problems that account to operate efficiently.